Laparoscopic repeat liver resection for hepatocellular carcinoma: a multicentre propensity score-based study. Issue 7 (29th January 2020) - Morise, Z; Aldrighetti, L; Belli, G; Ratti, F; Belli, A; Cherqui, D; Tanabe, M; Wakabayashi, G; Cheung, T T; Lo, C M; Tanaka, S; Kubo, S; et al.
Abstract: Background: In the absence of randomized controlled data and even propensity-matched data, indications for, and outcomes of, laparoscopic repeat liver resection for hepatocellular carcinoma (HCC) remain uncertain. This study aimed to clarify the current indications for laparoscopic repeat liver resection for HCC, and to evaluate outcomes. Methods: Forty-two liver surgery centres around the world registered patients who underwent repeat liver resection for HCC. Patient characteristics, preoperative liver function, tumour characteristics, surgical method, and short- and long-term outcomes were recorded. Results: Analyses showed that the laparoscopic procedure was generally used in patients with relatively poor performance status and liver function, but favourable tumour characteristics. Intraoperative blood loss (mean(s.d.) 254(551) versus 748(1128) ml; P < 0·001), duration of operation (248(156) versus 285(167) min; P < 0·001), morbidity (12·7 versus 18·1 per cent; P = 0·006) and duration of postoperative hospital stay (10·1(14·3) versus 11·8(11·8) days; P = 0·013) were significantly reduced for laparoscopic compared with open procedures, whereas survival time was comparable (median 10·04 versus 8·94 years; P = 0·297). Propensity score matching showed that laparoscopic repeat liver resection for HCC resulted in less intraoperative blood loss (268(730) versus 497(784) ml; P = 0·001) and a longer operation time (272(187) versus 232(129); P = 0·007) than the open approach, and similar survival time (12·55 versus 8·94 years; P = 0·086). Conclusion: Laparoscopic repeat liver resection is feasible in selected patients with recurrent HCC. Graphical Abstract: This report describes a propensity score matching analysis of open versus laparoscopic repeat liver resection. The laparoscopic procedure is generally used in patients with relatively low performance status and relatively poor liver function but favourable tumour characteristics. The present data indicate that laparoscopic repeat liver resection is feasible, yielding acceptable short- and long-term outcomes, for treatment of recurrent hepatocellular carcinoma in selected patients. ORLR-PSM, propensity score-matched open repeat liver resection group; LRLR-PSM, propensity score-matched laparoscopic repeat liver resection group. Selection is key